Wizerunek językowy młodego pokolenia w powieści Doroty Masłowskiej Kochanie, zabiłam nasze koty jako przykład lingua frankensteinia = The image of young generation's languge in Dorota Maslowska's novel Kochanie, zabiłam nasze koty as an example of lingua frankensteinia - Woźniak, Jesica (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to show the image of young generation?s language and a view at the issue of globalization of language communication in the novel of Dorota Masłowska Kochanie, zabiłam nasze koty. The goal of this article is to draw attention to language of this novel as an example of lingua frankensteinia. The article presents not only examples of language excerpted from novel, but also emphasizes role of the stylization of language layer that is supported by grotesquely outlined form of chic lit genre, highlighting at the same time the problem of monopolization of language by English language in postmodern world.
Keywords: Masłowska, Dorota (1983 -); lingua frankensteinia; globalizacja językowa; wizerunek językowy; młode pokolenie; language globalization; language image; young generation